Pengaruh Kepemimpinan Transformasional dan Keterlibatan Kerja terhadap Organizational Citizenship Behavior (OCB) melalui Mediator Kepuasan Kerja - Naimah, Muflikhatun; tentama, Fatwa tentama; Diah Sari, Erita Yuliasesti (Universitas Islam Indonesia, 2022)
Teachers of extraordinary school (SLB) have a heavier and more varied workload than general teachers. In addition of carrying out administrative works, extraordinary school teachers face challenges in educating children with special needs who also require special handling. Organizational Citizenship Behavior (OCB) is required to overcome this situation. This study aims to test the model of transformational leadership effect and job involvement on OCB with job satisfaction as a mediator of SLB teachers. Participants in this study was 88 SLB teachers from State Extraordinary School